Clinical significance of long non-coding RNA expression in esophageal cancer depending on the phenotype of the tumor stroma - O. V. Kovaleva; P. A. Podlesnaya; E. S. Kudinova; M. A. Rashidova; V. V. Mochalnikova; A. N. Gratchev (Успехи молекулярной онкологии, 2024)
Introduction. Esophageal squamous cell carcinoma is a dangerous oncological disease for which there are no relevant molecular-biological and biochemical markers for diagnosis, monitoring, and prognosis. Non-coding RNAs, whose aberrant expression is characteristic of many neoplasms may be promising candidate markers.Aim. To investigate the clinical significance of the expression of long non-coding RNAs (lncRNAs) SNGH18, LCAL1, IGFL2-AS1, LINC02301 and LINC01508 in esophageal squamous cell carcinoma depending on the phenotype of the tumor stroma.Materials and methods. The study included 17 patients with esophageal squamous cell carcinoma, who were examined and treated at the N.N. Blokhin National Medical Research Center of Oncology. Gene expression levels were assessed using real-time polymerase chain reaction. Immunohistochemical analysis was conducted to evaluate the expression of CD68, CD163 and inducible nitric oxide synthase. Statistical analysis of the obtained results was performed using GraphPad Prizm v. 10. Differences in lncRNA expression between tumor samples and conditionally normal tissues were assessed using the Wilcoxon test for paired samples. Correlation analysis was carried out by calculating Spearman’s correlation coefficient. Survival analysis was conducted using Kaplan–Meier survival curves. A p-value of less than 0.05 was considered statistically significant.Results. Aberrant expression of the lncRNAs LCAL1, LINC01508 and LINC02301 was observed in tumor tissue compared to conditionally normal tissue. Specifically, the expression of LCAL1 and LINC01508 was increased in tumor tissue (p = 0,001 and p = 0,007), while the expression of lncRNA LINC02301 was decreased (p = 0,004). The expression of lncRNAs SNGH18 and IGFL2-AS1 showed no significant changes. ROC-analysis indicated that examining these lncRNA expressions is not suitable for diagnosing esophageal squamous cell carcinoma. Clinical significance analysis revealed no correlation between the studied lncRNA expressions and the clinicopathological characteristics of the disease correlation analysis of the lncRNAs SNGH18, LCAL1, IGFL2-AS1, LINC02301 and LINC01508 with the phenotype of tumor stroma macrophages demonstrated that LINC01508 was significantly and positively correlated with both the total number of macrophages (r = 0.579; p = 0.017) and the number of macrophages with cytotoxic and immunosuppressive phenotypes (r = 0.567; p = 0.004 and r = 0.496; p = 0.045, accordingly). In contrast, LCAL1 expression was inversely correlated with the number of cytotoxic macrophages (r = –0.490; p = 0.037). Prognostic analysis revealed that only lncRNA IGFL2-AS1 expression was associated with favorable prognosis in esophageal squamous cell carcinoma (hazard ratio 0.374; p = 0.039).Conclusion. Long non-coding RNAs are important regulatory elements in both normal and tumor cells, offering certain advantages for the diagnosis of oncological diseases due to their high specificity and stability in both tissues and circulating body fluids. Growing evidence from scientific research highlights the potential clinical application of lncRNA expression analysis as markers for early diagnosis and as potential therapeutic targets. In this study, we conducted a retrospective investigation and determined the clinical significance of lncRNAs SNGH18, LCAL1, IGFL2-AS1, LINC02301, LINC01508 in esophageal squamous cell carcinoma, thereby expanding our understanding of the molecular changes observed in the development of this disease.